2006
DOI: 10.1007/s00127-006-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender in diagnosing early schizophrenia

Abstract: Patient gender in itself affects clinicians' diagnostic practice regarding schizophrenia, as schizophrenia diagnosis is given significantly more often to a male case description than to a female one, the descriptions being otherwise identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This finding is curious as most schizophrenia studies have not found a sex difference in mortality risk or have found a higher risk for males. However, one recent study from Norway 41 found that women with schizophrenia who had been hospitalized showed an increased difference in mortality risk relative to the general population in the period 1992-2006 compared with an earlier period, 1980-1992; in the recent time period, women were also found to have an increase in absolute mortality compared with the earlier period, approaching that of men. It has also been noted that women with schizophrenia may be at particular risk for cardiovascular disease and associated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is curious as most schizophrenia studies have not found a sex difference in mortality risk or have found a higher risk for males. However, one recent study from Norway 41 found that women with schizophrenia who had been hospitalized showed an increased difference in mortality risk relative to the general population in the period 1992-2006 compared with an earlier period, 1980-1992; in the recent time period, women were also found to have an increase in absolute mortality compared with the earlier period, approaching that of men. It has also been noted that women with schizophrenia may be at particular risk for cardiovascular disease and associated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…According to Høye et al [10], psychiatrists tend to diagnose schizophrenia more often in men than women, so women might have been diagnosed with other psychoses. Therefore, the diagnosis of other psychoses should be studied in relation to prevalence and service use by gender.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications from the present study have shown that participants with alcohol related disorders in this sample were older than those with drug use disorders [34]. The variable gender was not significant, which is interesting since prior studies have found that the gender of the patient is an important factor with respect to both the distribution of mental disorders [10] and diagnostic practice [38]. …”
Section: Discussionmentioning
confidence: 43%
“…In this study, we wanted to investigate to which extent co-occurring psychiatric disorders were diagnosed in a clinical population of substance abusers. We were also interested in factors influencing diagnostic practice, and to which extent diagnostic practice varied with the variables that we had data on [38]. We hypothesized that there would be differences in diagnostic practice according to which extent a systematic diagnostic tool (i.e.…”
Section: Introductionmentioning
confidence: 99%